Impact of optimization algorithms on hybrid indoor positioning based on GSM and Wi‐Fi signals. (13th July 2016) - Machaj, Juraj; Brida, Peter
Summary: In the recent time indoor positioning becomes an extremely hot topic between researchers worldwide. This is mainly because of lack of available positioning solutions in the indoor environment and possibility to offer novel services based on location of users. Such services can also open new markets for service providers and thus increase their income. In this paper we will focus on application of optimization algorithms on performance of hybrid indoor positioning system, which utilize radio signals from both Global System for Mobile communication and Wi‐Fi networks simultaneously. The system is based on fingerprinting framework, which is widely used for indoor positioning because of its performance in strong multipath environment. Tests of the optimization algorithms were performed via simulations that were performed using simulation model created in Matlab environment. Copyright © 2016 John Wiley & Sons, Ltd.